Aptly chosen, effectively emphasizing the action and mechanism of antimycin A1 - Zhu, Linyan; Weng, Chenhong; Shen, Xiaoman; Zhu, Xiangdong (Frontiers in Microbiology, 2024)
Rhizoctonia solani Kühn , a plant pathogenic fungus that can cause diseases in multiple plant species is considered one of the common and destructive pathogens in many crops.This study investigated the action of antimycin A 1, which was isolated from Streptomyces AHF-20 found in the rhizosphere soil of an ancient banyan tree, on Rhizoctonia solani and its mechanism.The inhibitory effect of antimycin A 1 on R. solani was assessed using the comparative growth rate method.The results revealed that antimycin A 1 exhibited a 92.55% inhibition rate against R. solani at a concentration of 26.66 μg/mL, with an EC 50 value of 1.25 μg/mL. To observe the impact of antimycin A 1 on mycelial morphology and ultrastructure, the fungal mycelium was treated with 6.66 μg/mL antimycin A 1 , and scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were employed. SEM analysis demonstrated that antimycin A 1 caused mycelial morphology to become stripped, rough, and folded. The mycelium experienced severe distortion and breakage, with incomplete or locally enlarged ends, shortened branches, and reduced numbers. TEM observation revealed thickened cell walls, indistinct organelle boundaries, swollen mitochondria, exosmotic substances in vesicles, slow vesicle fusion, and cavitation. Real-time quantitative PCR and enzyme activity assays were conducted to further investigate the impact of antimycin A 1 on mitochondria. The physiological and biochemical results indicated that antimycin A 1 inhibited complexes III and IV of the mitochondrial electron transport chain. RT-PCR analysis demonstrated that antimycin A 1 controlled the synthesis of relevant enzymes by suppressing the transcription levels of ATP6, ATP8, COX3, QCR6, CytB, ND1, and ND3 genes in mitochondria. Additionally, a metabolomic analysis revealed that antimycin A 1 significantly impacted 12 metabolic pathways. These pathways likely experienced alterations in their metabolite profiles due to the inhibitory effects of antimycin A 1 . Consequently, the findings of this research contribute to the potential development of novel fungicides.